Preparedness Of Students In Social Norms To Entrepreneurial Intentions (Case Studies On Students) - Arfian; Ananda Khoirunisa Putri Fauzi; Firly Fadillah; Sandra Aisyah Azahra; Amara Mutiara Santoso (Insight School Academy, 2024)
Problem Identification : Social norms play an important role in shaping the perception and intention of being an entrepreneur, because they are external factors that influence an individual's attitude toward entrepreneurship. Objective : The study aims to examine the influence of social and entrepreneurial education norms on student interests in entrepreneurship, as well as how these factors can be integrated into educational programmes to enhance such interests. Method : Research using a method of literature study involves collecting data from various sources such as ebooks, journals, scientific articles, and online sources related to the concept being studied. The focus is on students who are active or interested in entrepreneurship. Findings : Entrepreneurship education plays an important role in promoting entrepreneurial intentions among students, with social norms as one of its influences. This study emphasizes that entrepreneurhood education, in particular that involves the formation of positive attitudes, is a key factor in increasing enterprise intensity. Research Implications : Through the study of literature, researchers gain a better understanding of the concept of student preparedness for social entrepreneurship. This involves examining relevant theories, conceptual frameworks, and related previous research results. The researchers were then able to identify research variables such as social norms, self-efficacy, and motivations that influenced students' readiness for entrepreneurship. Value of Research : The results of this research are both theoretical and practical for other researchers by providing important information. In addition, the results support the formation and development of discourse as well as science.